Method for inhibiting flotation of sulphide ore by utilizing galvanic corrosion effect of scrap steel-sulphide ore
Through the galvanic corrosion of scrap steel and sulfide ore, hydrophilic iron oxides are generated, and the flotation of sulfide ore is inhibited, the problem of gangue mineral influence during sulfide ore flotation is solved, and efficient resource utilization and environmental protection are achieved.
Patent Information
- Application Number
- CN202411582677.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-07
AI Technical Summary
During the flotation process of sulfide ore, the existence of gangue minerals leads to a reduction in the quality of the target minerals and an increase in smelting costs, and it is difficult for the prior art to effectively recover and utilize sulfide ore.
By utilizing the galvanic corrosion between scrap steel and sulfide ore, hydrophilic iron oxides are generated on the surface of sulfide ore, and their floatability is reduced, thereby inhibiting the flotation of sulfide ore.
Effectively inhibit the flotation of sulfide ore, reduce the use of flotation agents, improve resource utilization, promote the high-value utilization of scrap steel, and reduce environmental pollution.
Smart Images

Figure CN119387041A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mineral flotation, and in particular to a method for inhibiting the flotation of sulfide ore by utilizing the galvanic corrosion of scrap steel and sulfide ore. Background Art
[0002] Sulfide ore, as an important non-ferrous metal resource, plays an important role in economic development. With the continuous advancement of science and technology, the demand for molybdenum, copper, iron, etc. is also increasing. Sulfide ore is the main form of non-ferrous metal elements and one of the most important ores for industrial extraction of non-ferrous metal elements, with high economic value.
[0003] However, in the process of mining and processing sulfide ores, many gangue minerals are often associated, affecting the quality and value of the target minerals. At the same time, with the continuous development of mineral resources, the easy-to-select rich ore resources are gradually exhausted, and the sulfide ore deposits are characterized by "poor, fine, and mixed", which makes it difficult to effectively recycle the target minerals during the flotation process. Moreover, in the flotation process, some gangue minerals are similar in nature to sulfide ores, which will increase the use of flotation agents and increase the difficulty of the flotation process. At the same time, the presence of gangue minerals will lead to a decrease in the quality of the concentrate and an increase in smelting costs.
[0004] Therefore, the industry is in urgent need of a new technology for flotation of sulfide ores. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a method for inhibiting the flotation of sulfide ore by utilizing the galvanic corrosion of scrap steel and sulfide ore. Because the use of corrosive materials such as forged steel to grind sulfide ore will cause galvanic corrosion between the sulfide ore and the grinding medium material, so that hydrophilic iron oxide substances are generated on the surface of the sulfide ore, thereby reducing the floatability of the sulfide ore. In addition, sulfide ore usually has good semiconductor properties, and galvanic corrosion is easily caused between it and iron-based materials. Therefore, the galvanic corrosion of scrap steel and sulfide ore can change the surface flotation performance of sulfide ore and inhibit the flotation of sulfide ore. At the same time, developing new ways to utilize scrap steel in the flotation of sulfide ore will help promote the resource utilization and high-value utilization of scrap steel, and can also reduce the use of flotation agents and protect the environment.
[0006] Scrap steel refers to scrapped steel products that have lost their original use value or steel products that have been replaced for various reasons, as well as waste, scraps and steel-containing waste generated in the production of steel materials and the processing and manufacturing of steel products. As a type of industrial waste, it is an important resource for the development of circular economy. It has a large output and occupies a large amount of land resources, which plays a very important role in both environmental protection and economic development. The current utilization method is mainly to recycle valuable elements from scrap steel.
[0007] To achieve the above object, the present invention provides a method for inhibiting the flotation of sulfide ore by utilizing the galvanic corrosion of scrap steel and sulfide ore, which specifically comprises the following steps: Step 1: cleaning the surface of the scrap steel material; the scrap steel material is easily corrosive scrap steel; Step 2: adding mineral processing return water to the sulfide ore sample to be processed to prepare sulfide ore slurry; placing the sulfide ore slurry between two pieces of scrap steel obtained in step 1, so that the sulfide ore slurry is in full contact with the clean surface of the scrap steel, adding mineral processing return water to the sulfide ore slurry to be processed, so that galvanic corrosion occurs fully between the ore sample and the scrap steel, and obtaining a sulfide ore mineral sample after galvanic corrosion; Step 3: Transfer the sulfide ore sample obtained in step 2 to a flotation tank for flotation, control the stirring speed to be constant, add flotation reagents after stirring for a certain period of time to flotate the sulfide ore, and obtain flotation concentrate and tailings products.
[0008] Furthermore, in step one, the scrap steel material is pure iron scrap steel, low carbon steel scrap steel, medium carbon steel scrap steel or high carbon steel scrap steel.
[0009] Furthermore, in step one, the surface of the scrap steel material is cleaned, specifically: ultrasonic cleaning and polishing of the scrap steel material surface to remove the oxide film and oil stains and other pollutants on the scrap steel surface, so that the scrap steel exposes a fresh surface.
[0010] Furthermore, in step one, for the severely oxidized scrap steel material, the surface of the scrap steel is derusted by shot blasting, high-pressure water jet derusting or laser derusting to ensure that the clean surface of the scrap steel is exposed.
[0011] Furthermore, in step 2, the moisture content of the sulfide ore slurry during the galvanic corrosion process is controlled within the range of 20% - 60%, the galvanic corrosion temperature is 20-80°C, and the galvanic corrosion time is 10-50 min.
[0012] Furthermore, in step 2, an electric heater or a solar heater is used to maintain the temperature of the slurry within the range of 20-80°C during the galvanic corrosion process.
[0013] Furthermore, in step 2, during the galvanic corrosion treatment, the slurry between the two scrap steels is evenly stirred once every 3-10 minutes, and stirred 1-3 times during the galvanic corrosion, with a stirring time of 1 - 3 minutes. After stirring, the slurry is evenly applied on the clean surface of the scrap steel.
[0014] Furthermore, in step three, the flotation agent is MIBC (methyl isobutyl carbinol) frother.
[0015] Furthermore, in step three, the amount of flotation reagent added is 2-15 g / t.
[0016] The present invention has the following beneficial effects: 1. The present invention utilizes the semiconductor properties of sulfide ore and the corrosion properties of scrap steel. After the sulfide ore and scrap steel undergo galvanic corrosion, a large number of rough, flaky corrosion zones will form on the surface of the sulfide ore, and a large number of hydrophilic iron oxides will be generated, which will weaken its good hydrophobic properties and make it hydrophilic, effectively inhibiting the sulfide ore. In particular, for insulating minerals such as talc, galvanic corrosion will not occur between them and iron-based materials. However, sulfide minerals such as molybdenite have semiconductor properties, and significant galvanic corrosion will occur between them and iron-based materials. Therefore, it is possible to utilize galvanic corrosion to strengthen the flotation separation of sulfide minerals such as molybdenite and insulating minerals such as talc.
[0017] The specific principle is as follows: When galvanic corrosion occurs between scrap steel and sulfide minerals, the scrap steel corrodes as an anode, releasing Fe through reaction equations (1) and (2). 2+ or Fe 3+ These iron ions will further form iron oxides in the slurry aqueous solution; and the elemental sulfur on the surface of the sulfide ore may also corrode as an anode, releasing and , and hydroxides are formed on the surface of sulfide ore: Anode reaction formula: Fe → Fe 2+ +2e - (1) Fe 2+ → Fe 3+ + e - (2) (3) (4) The electrons released by anodic corrosion are consumed by dissolved oxygen on the surface of the sulfide ore through reaction (3): Cathode reaction: O2 + 2H2O + 4e - → 4OH - (5).
[0018] Therefore, the scrap steel-molybdenite galvanic corrosion can change the surface chemical composition of sulfide minerals and affect the surface activity of minerals. In addition, the oxidation products such as Fe(OH)3 produced during the galvanic corrosion process will cover the mineral surface, making the mineral surface hydrophilic.
[0019] 2. The present invention uses scrap steel as a reaction material for the first time, and utilizes it to produce galvanic corrosion with sulfide ore, thereby reducing the surface sulfur content, adsorbing and forming a large amount of iron oxide, improving the surface hydrophilicity of sulfide ore, and inhibiting the flotation of sulfide ore. The method of the present invention is applicable to most sulfide ores. At present, the sorting process for flotation recovery of sulfide ore is complicated, the amount of reagents used is large, and the processing cost is high. The present invention has a strong inhibitory effect on sulfide ore, strong pertinence, good selectivity, obvious effect, simple operation, and can promote the resource and high-value utilization of scrap steel, turning waste into treasure, saving costs, and being economical and environmentally friendly.
[0020] 3. The method of the present invention provides a new high-value utilization method for scrap steel, which is conducive to promoting the sustainable development of the steel industry and the sulfide ore flotation industry. The total amount of scrap steel resources available in my country's steel industry will reach 290 million to 310 million tons in 2030. The recycling of scrap steel can play a very important role in both environmental protection and economic development. At present, scrap steel is mainly recycled as a key raw material for steelmaking. Developing a new utilization method for scrap steel in sulfide ore flotation will help promote the resource utilization and high-value utilization of scrap steel.
[0021] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is a scanning electron microscope image of molybdenite before galvanic corrosion using pure iron scrap in implementation case 1; Figure 2 This is a scanning electron microscope image of molybdenite after galvanic corrosion using pure iron scrap steel in implementation case 1; Figure 3 This is the EDS spectrum of molybdenite before galvanic corrosion using pure iron scrap in Case 1; Figure 4 This is the EDS spectrum of molybdenite after galvanic corrosion using pure iron scrap in Case 1. DETAILED DESCRIPTION
[0023] The embodiments of the present invention are described clearly and completely below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain and illustrate the present invention and are not used to limit the present invention.
[0024] Implementation Case 1 The ore sample molybdenite single mineral in this implementation case was taken from Hunan Province, China. The mineral was first crushed to -1 mm and then sorted and impurities were removed. The resulting concentrate was ground by a sealed test sample crusher, and mineral particles with a particle size of -75 μm+45 μm were collected by a vibrating screen for testing. The sample was chemically analyzed and the purity of the molybdenite was 97.55%, and it also contained trace amounts of Cu, Fe and Bi elements.
[0025] The galvanic corrosion materials used in this implementation case are: pure iron scrap (carbon content: <0.006%), low carbon steel scrap (carbon content: <0.22%), high carbon steel scrap (carbon content: 0.8-0.9%), and corrosion-resistant stainless steel scrap. Before use, the scrap steel surface was ultrasonically cleaned and polished, and wiped clean with a clean paper towel.
[0026] Galvanic corrosion treatment: add beneficiation return water to 1 g of molybdenite slurry to be treated, so that the water content of the slurry is 50% during the galvanic corrosion process; use an electric heater to keep the slurry temperature at about 50 °C; place the molybdenite slurry between the clean surfaces of two horizontally placed scrap steels, so that the molybdenite slurry is in full contact with the clean surfaces of the scrap steels, and galvanic corrosion occurs for 20 min; during the galvanic corrosion process, stir the slurry between the two scrap steels once every 10 minutes, stir once during the galvanic corrosion, and stir for 1 minute. After stirring, apply the slurry evenly on the clean surface of the scrap steel to ensure that the molybdenite slurry is in full contact with the clean surface of the scrap steel, so that the molybdenite and the scrap steel are fully galvanically corroded. The time consumed in the stirring process is not counted in the galvanic corrosion time, and a molybdenite mineral sample after galvanic corrosion is obtained; Flotation process: 1 g of molybdenite sample treated by galvanic corrosion was transferred to a 45 ml flotation cell, and an appropriate amount of water was added. After stirring for a certain period of time, 15 g / t MIBC frother was added, and the upper foam was manually scraped at a uniform speed. The flotation temperature was room temperature (20 °C), and the recovery rate was calculated based on the concentrate and tailings after flotation drying.
[0027] Scanning electron microscope tests were performed on molybdenite before and after galvanic corrosion using pure iron scrap steel. The results are as follows: Figure 1 and Figure 2 shown. Figure 1 This is a scanning electron microscope image of molybdenite before galvanic corrosion. Figure 2 The following is a scanning electron microscope image of molybdenite after galvanic corrosion. The EDS spectrum test was performed on molybdenite before and after galvanic corrosion using pure iron scrap steel. The results are as follows: Figure 3 and Figure 4 shown. Figure 3 This is the EDS spectrum of molybdenite before galvanic corrosion. Figure 4This is the EDS spectrum of molybdenite after galvanic corrosion.
[0028] Depend on Figure 1 It can be seen that before the galvanic corrosion, the surface of molybdenite is relatively flat and smooth. Figure 3 The EDS energy spectrum found that the atomic content ratio of Mo and S elements is close to 1:2, indicating that the surface material of molybdenite is mainly in the form of MoS2, and it only contains trace amounts of Fe. It can also be seen from the energy spectrum that the surface of molybdenite contains a small amount of O, which may be oxygen adsorbed on the surface of molybdenite or in oxides formed by self-oxidation of molybdenite when exposed to air.
[0029] Depend on Figure 2 It can be seen that after the galvanic corrosion, the surface of molybdenite has undergone great changes. From the morphology, it is found that there are a large number of rough, scaly corrosion zones on the surface of molybdenite, and white flocs are also adsorbed. At the same time, combined with Figure 4 From the EDS spectrum, it can be seen that the atomic content ratio of Mo and S on the surface after corrosion is close to 1:1.5, and it is also found that O and Fe elements have increased significantly, which may be due to the formation of molybdenum oxides on the surface of molybdenite and the adsorption of a large amount of iron oxides. From the atomic content of Mo and S elements before and after galvanic corrosion, the Mo and S elements of molybdenite are reduced after galvanic corrosion, and the S element is reduced more, which may indicate that sulfur vacancies are formed on the surface of molybdenite after galvanic corrosion, providing adsorption sites for the adsorption of iron oxides. This may be one of the reasons why the hydrophobicity of the molybdenite surface changes after galvanic corrosion and the flotation recovery rate decreases.
[0030] The recovery rate of molybdenite before and after galvanic corrosion between molybdenite and scrap steel is shown in Table 1.
[0031] Table 1 It can be seen from Table 1 that the use of easily corrosive scrap steel materials such as pure iron can inhibit the flotation of molybdenite and significantly reduce the recovery rate of molybdenite. This may be because low-carbon steel, high-carbon steel and pure iron do not have corrosion resistance, resulting in significant galvanic corrosion between molybdenite and them, which has a significant impact on the flotation recovery of molybdenite. The use of corrosion-resistant stainless steel scrap has little effect on the floatability of molybdenite. This may be because stainless steel has good corrosion resistance, resulting in no significant galvanic corrosion with molybdenite in a shorter contact time, thus having no significant impact on the flotation recovery of molybdenite.
[0032] Implementation Case 2 The ore sample molybdenite single mineral in this implementation case was taken from Hunan Province, China. The mineral was first crushed to -1 mm and then sorted and impurities were removed. The resulting concentrate was ground by a sealed test sample crusher, and mineral particles with a particle size of -75 μm+45 μm were collected by a vibrating screen for testing. The sample was chemically analyzed and the purity of the molybdenite was 97.55%, and it also contained trace amounts of Cu, Fe and Bi elements.
[0033] The galvanic corrosion material used in this embodiment is pure iron scrap steel. Before use, the scrap steel surface is ultrasonically cleaned and polished, and wiped clean with a clean paper towel.
[0034] Galvanic corrosion treatment: Adding ore dressing return water to 1 g of molybdenite slurry to be treated, so that the water content of the slurry of molybdenite during the galvanic corrosion process is 20%, 33%, 60%, and 70%, and at the same time, setting the slurry without adding ore dressing return water (i.e., the slurry water content is 0); using an electric heater to maintain the slurry temperature at 20 ° C; placing the molybdenite slurry between the clean surfaces of two horizontally placed scrap steels, so that the molybdenite slurry is in full contact with the clean surfaces of the scrap steels, and galvanic corrosion occurs, and the galvanic corrosion time is 20 min; during the galvanic corrosion process, the slurry between the two scrap steels is evenly stirred once every 10 minutes, and the stirring time is 1 minute. After stirring, the slurry is evenly applied to the clean surface of the scrap steel to ensure that the molybdenite slurry is in full contact with the clean surface of the scrap steel, so that the molybdenite and the scrap steel are fully galvanically corroded, and the time consumed in the stirring process is not counted in the galvanic corrosion time, and the molybdenite mineral sample after galvanic corrosion is obtained; Flotation process: 1 g of molybdenite sample treated by galvanic corrosion was transferred to a 45 ml flotation tank, and an appropriate amount of water was added. After stirring for a certain period of time, 15 g / t MIBC frother was added, and the upper foam was manually scraped at a uniform speed. The flotation temperature was room temperature (20 ° C), and the recovery rate was calculated based on the concentrate and tailings after flotation drying. The change of the recovery rate of molybdenite with the galvanic corrosion time after galvanic corrosion occurred between molybdenite and scrap steel is shown in Table 2.
[0035] Table 2 As shown in Table 2, in the absence of water (water content 0%), the flotation recovery rate of molybdenite is 88.29%, which is close to the flotation recovery rate of molybdenite without galvanic corrosion (89.67%). This may be because there is a lack of conductive medium in the galvanic corrosion system in the absence of water, so that pure iron and molybdenite do not undergo galvanic corrosion. When an aqueous solution medium (water content 20%) is added during the galvanic corrosion process, the flotation recovery rate of molybdenite after galvanic corrosion drops to 65.18%, which indicates that the solution medium is a necessary condition for galvanic corrosion between scrap steel and molybdenite. And as the water content increases to 33% and 60% respectively, the recovery rate of molybdenite after galvanic corrosion decreases to 45.61% and 33.08%. When the water content continues to increase to 70%, the flotation recovery rate of molybdenite increases instead, which indicates that the appropriate amount of water content is crucial in the galvanic corrosion process between pure iron and molybdenite.
[0036] Implementation Case 3 The ore sample molybdenite single mineral in this implementation case was taken from Hunan Province, China. The mineral was first crushed to -1 mm and then sorted and impurities were removed. The resulting concentrate was ground by a sealed test sample crusher, and mineral particles with a particle size of -75 μm+45 μm were collected by a vibrating screen for testing. The sample was chemically analyzed and the purity of the molybdenite was 97.55%, and it also contained trace amounts of Cu, Fe and Bi elements.
[0037] The galvanic corrosion material used in this embodiment is pure iron scrap steel. Before use, the scrap steel surface is ultrasonically cleaned and polished, and wiped clean with a clean paper towel.
[0038] Galvanic corrosion treatment: Adding ore dressing return water to 1 g of molybdenite slurry to be treated makes the water content of the slurry of molybdenite at 33% during the galvanic corrosion process; using an electric heater to keep the slurry temperature at 20 °C; placing the molybdenite slurry between the clean surfaces of two horizontally placed scrap steels, so that the molybdenite slurry is in full contact with the clean surfaces of the scrap steels, and galvanic corrosion occurs, and the galvanic corrosion time is 10 min, 20 min, 30 min, and 40 min, respectively; during the galvanic corrosion process, the slurry between the two scrap steels is stirred evenly once every 10 minutes, and the stirring time is 1 minute. After stirring, the slurry is evenly applied to the clean surface of the scrap steel to ensure that the molybdenite slurry is in full contact with the clean surface of the scrap steel, so that the molybdenite and the scrap steel are fully galvanically corroded, and the time consumed in the stirring process is not counted in the galvanic corrosion time, and a molybdenite mineral sample after galvanic corrosion is obtained; Flotation process: 1 g of molybdenite sample after galvanic corrosion treatment was transferred to a 45 ml flotation tank, and an appropriate amount of water was added. After stirring for a certain period of time, 15 g / t MIBC frother was added, and the upper foam was manually scraped at a uniform speed. The flotation temperature was room temperature (20 ° C), and the recovery rate was calculated based on the concentrate and tailings after flotation drying. The change of the recovery rate of molybdenite with the galvanic corrosion time after galvanic corrosion occurred between molybdenite and scrap steel is shown in Table 3.
[0039] Table 3 As shown in Table 3, when the galvanic corrosion time is 5 minutes, the flotation recovery rate of molybdenite is 67.29%, which indicates that galvanic corrosion has begun to occur between pure iron and molybdenite in a short time, and also affects the surface hydrophobicity of molybdenite; but due to the short contact time, the reaction between pure iron scrap and molybdenite is not sufficient, so that the mineral recovery rate only slightly decreases. As the galvanic corrosion time increases, the flotation recovery rate of molybdenite after galvanic corrosion gradually decreases, which is 42.36%, 31.62%, 31.88%, and 32.09% respectively. This shows that allowing molybdenite to fully contact with scrap steel for a certain period of time, so that galvanic corrosion occurs between molybdenite and scrap steel, can significantly reduce the recovery rate of molybdenite.
[0040] Implementation Case 4 The ore sample molybdenite single mineral in this implementation case was taken from Hunan Province, China. The mineral was first crushed to -1 mm and then sorted and impurities were removed. The resulting concentrate was ground by a sealed test sample crusher, and mineral particles with a particle size of -75 μm+45 μm were collected by a vibrating screen for testing. The sample was chemically analyzed and the purity of the molybdenite was 97.55%, containing trace amounts of Cu, Fe and Bi elements.
[0041] The galvanic corrosion material used in this embodiment is pure iron scrap steel. Before use, the scrap steel surface is ultrasonically cleaned and polished, and wiped clean with a clean paper towel.
[0042] Galvanic corrosion treatment: Adding ore dressing return water to 1 g of molybdenite slurry to be treated, so that the water content of the slurry of molybdenite is 33% during the galvanic corrosion process; using an electric heater to keep the slurry temperature at 20 ℃, 30 ℃, and 50 ℃ in sequence; placing the molybdenite slurry between the clean surfaces of two horizontally placed scrap steels, so that the molybdenite slurry is in full contact with the clean surfaces of the scrap steels, and galvanic corrosion occurs, and the galvanic corrosion time is 20 min; during the galvanic corrosion process, the slurry between the two scrap steels is evenly stirred once every 10 minutes, and the stirring time is 1 minute. After stirring, the slurry is evenly applied to the clean surface of the scrap steel to ensure that the molybdenite slurry is in full contact with the clean surface of the scrap steel, so that the molybdenite and the scrap steel are fully galvanically corroded, and the time consumed in the stirring process is not counted in the galvanic corrosion time, and a molybdenite mineral sample after galvanic corrosion is obtained; Flotation process: 1 g of molybdenite sample treated by galvanic corrosion was transferred to a 45 ml flotation tank, and an appropriate amount of water was added. After stirring for a certain period of time, 15 g / t MIBC frother was added, and the upper foam was manually scraped at a uniform speed. The flotation temperature was room temperature (20 ° C), and the recovery rate was calculated based on the concentrate and tailings after flotation drying. The recovery rate of molybdenite after galvanic corrosion between molybdenite and scrap steel varies with the pulp temperature as shown in Table 4.
[0043] Table 4 As shown in Table 4, the slurry temperature in the present invention has a great influence on the galvanic corrosion process of molybdenite. When the slurry temperature is 10°C, the flotation recovery rate of molybdenite is 58.16%. This may be because the ion transfer in the reaction process is not active enough when the temperature is too low, which makes the reaction process slow and the flotation recovery rate is relatively high. When the slurry temperature is 20°C, the flotation recovery rate of molybdenite is 45.21%. When the slurry temperature is increased to 30°C, the flotation recovery rate of molybdenite drops to 27.38%. When the slurry temperature continues to increase to 50°C, it can be found that the flotation recovery rate of molybdenite is reduced to 18.47%; this shows that the slurry temperature can promote the galvanic corrosion between molybdenite and scrap steel, accelerate the generation and adsorption of ions in the galvanic corrosion process, and enhance the inhibitory effect of the galvanic corrosion between molybdenite and scrap steel on molybdenite.
[0044] Implementation Case 5 The single mineral chalcopyrite in the ore sample of this implementation case was taken from Guangxi Zhuang Autonomous Region, China. The ore was first crushed to -1 mm and then sorted and impurities were removed. The resulting concentrate was ground by a sealed test sample crusher, and mineral particles with a particle size of -75 μm+45 μm were collected by a vibrating screen for testing. The sample was chemically analyzed and the purity of chalcopyrite was 95.7%, and the rest were gangue minerals such as silicon dioxide.
[0045] The galvanic corrosion materials used in this embodiment are: pure iron scrap, low carbon steel scrap and high carbon steel scrap. Before use, the scrap steel surface is ultrasonically cleaned and polished, and wiped clean with a clean paper towel.
[0046] Galvanic corrosion treatment: Adding beneficiation return water to 1 g of the chalcopyrite slurry to be treated, so that the water content of the chalcopyrite slurry is 33% during the galvanic corrosion process; using an electric heater to maintain the slurry temperature at about 20 ° C; placing the chalcopyrite slurry between the clean surfaces of two horizontally placed scrap steels, so that the chalcopyrite slurry is in full contact with the clean surfaces of the scrap steels, and galvanic corrosion occurs, and the galvanic corrosion time is 10 min; during the galvanic corrosion process, the slurry between the two scrap steels is stirred evenly once every 5 minutes, and stirred once during the galvanic corrosion, and the stirring time is 1 minute. After stirring, the slurry is evenly applied to the clean surface of the scrap steel to ensure that the chalcopyrite slurry is in full contact with the clean surface of the scrap steel, so that the chalcopyrite and the scrap steel are fully galvanically corroded, and the time consumed in the stirring process is not counted in the galvanic corrosion time, and the chalcopyrite mineral sample after galvanic corrosion is obtained; Flotation process: 1 g of chalcopyrite sample treated by galvanic corrosion was transferred to a 45 ml flotation tank, and an appropriate amount of water was added. After stirring for a certain period of time, 15 g / t MIBC frother was added, and the upper foam was manually scraped at a uniform speed. The flotation temperature was room temperature (20 ° C), and the recovery rate was calculated based on the concentrate and tailings after flotation drying. The experimental results are shown in Table 5.
[0047] Table 5 It can be seen from Table 5 that the present invention can significantly reduce the recovery rate of chalcopyrite.
[0048] Implementation Case 6 The single mineral pyrite sample in this implementation case was taken from Guangxi Zhuang Autonomous Region, China. The ore was first crushed to -1 mm and then sorted and impurities were removed. The resulting concentrate was ground by a sealed test sample crusher, and mineral particles with a particle size of -75 μm+35 μm were collected by a vibrating screen for testing. The sample was chemically analyzed and the purity of pyrite was 97.28%, and the rest were gangue minerals such as silica.
[0049] The galvanic corrosion materials used in this embodiment are: pure iron scrap, low carbon steel scrap and high carbon steel scrap. Before use, the scrap steel surface is ultrasonically cleaned and polished, and wiped clean with a clean paper towel.
[0050] Galvanic corrosion treatment: Adding ore dressing return water to 1 g of the pyrite slurry to be processed, so that the water content of the pyrite slurry is 50% during the galvanic corrosion process; using an electric heater to maintain the slurry temperature at about 30°C; placing the pyrite slurry between the clean surfaces of two horizontally placed scrap steels, so that the pyrite slurry is in full contact with the clean surfaces of the scrap steels, and galvanic corrosion occurs, and the galvanic corrosion time is 20 minutes; during the galvanic corrosion process, the slurry between the two scrap steels is stirred evenly once every 5 minutes, and stirred once during the galvanic corrosion, and the stirring time is 1 minute. After stirring, the slurry is evenly applied to the clean surface of the scrap steel to ensure that the pyrite slurry is in full contact with the clean surface of the scrap steel, so that the pyrite and the scrap steel are fully galvanically corroded, and the time consumed in the stirring process is not counted within the galvanic corrosion time, and a pyrite mineral sample after galvanic corrosion is obtained; Flotation process: 1 g of pyrite sample treated by galvanic corrosion was transferred to a 45 ml flotation tank, and an appropriate amount of water was added. After stirring for a certain period of time, 15 g / t MIBC frother was added, and the upper foam was manually scraped at a uniform speed. The flotation temperature was room temperature (20 ° C), and the recovery rate was calculated based on the concentrate and tailings after flotation drying. The experimental results are shown in Table 6.
[0051] Table 6 It can be seen from Table 6 that the present invention can significantly reduce the recovery rate of pyrite.
[0052] Implementation Case 7 The single mineral talc sample in this implementation case was taken from Hunan Province, China. The ore was first crushed to -1 mm and then sorted and impurities were removed. The resulting concentrate was ground by a sealed test sample crusher, and mineral particles with a particle size of -75 μm+45 μm were collected by a vibrating screen for testing. The sample was chemically analyzed and the purity of the talc was 96.12%, containing trace amounts of aluminum oxide and iron.
[0053] The galvanic corrosion materials used in this embodiment are: pure iron scrap, low carbon steel scrap and high carbon steel scrap. Before use, the scrap steel surface is ultrasonically cleaned and polished, and wiped clean with a clean paper towel.
[0054] Galvanic corrosion treatment: Adding ore dressing return water to 1 g of talc slurry to be treated, so that the water content of the talc slurry is 50% during the galvanic corrosion process; using an electric heater to maintain the slurry temperature at about 20 ° C; placing the talc slurry between the clean surfaces of two horizontally placed scrap steels, so that the talc slurry is in full contact with the clean surface of the scrap steel, and galvanic corrosion is carried out for 20 min; during the galvanic corrosion process, the slurry between the two scrap steels is stirred once every 5 minutes, and stirred 3 times during the galvanic corrosion process, and the stirring time is 1 minute. After stirring, the slurry is evenly applied to the clean surface of the scrap steel to ensure that the talc slurry is in full contact with the clean surface of the scrap steel, so that the talc is in full contact with the scrap steel, and the time consumed in the stirring process is not counted in the galvanic corrosion time, and a talc mineral sample treated with galvanic corrosion is obtained; Flotation process: 1 g of talc sample treated by galvanic corrosion was transferred to a 45 ml flotation tank, and an appropriate amount of water was added. After stirring for a certain period of time, 15 g / t MIBC frother was added, and the upper foam was manually scraped at a uniform speed. The flotation temperature was room temperature (20 °C), and the recovery rate was calculated based on the concentrate and tailings after flotation drying. The experimental results are shown in Table 7.
[0055] Table 7 As can be seen from Table 7, the present invention has almost no effect on the floatability of talc. This may be because talc is an insulator and will not cause galvanic corrosion when in contact with scrap steel, so its surface hydrophobicity is not affected and still maintains good flotation performance.
[0056] In summary, the present invention has established a new and efficient method for inhibiting the flotation of sulfide ores, expanded new ways of utilizing scrap steel in the flotation of sulfide ores, and improved the utilization value of scrap steel; at the same time, it provides an effective technical support for reducing the hazards of flotation agents and recycling resources for mineral processing plants, metallurgical plants and related industries, thereby improving resource utilization; and the present invention is easy to operate, has low requirements for equipment, has obvious effects, saves costs, and protects the environment. In addition, the present invention provides a new and feasible separation technology method for the flotation separation of sulfide ores and insulating minerals such as talc, such as the flotation separation of molybdenite and talc, and the flotation separation of pyrite and coal.
[0057] The specific embodiments of the present invention disclosed above are only used to help explain the present invention. However, the protection scope of the present invention is not limited thereto. As described in the contents of this specification, many modifications and changes can be made accordingly. Any modification, equivalent substitution and improvement made by any technician familiar with the technical scope disclosed by the present invention within the spirit and principle of the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for inhibiting the flotation of sulfide ore by utilizing the galvanic corrosion of scrap steel and sulfide ore, characterized in that: The following steps are involved: Step 1: cleaning the surface of the scrap steel material; the scrap steel material is easily corrosive scrap steel; Step 2: adding mineral processing return water to the sulfide ore sample to be processed to prepare sulfide ore slurry; placing the sulfide ore slurry between two pieces of scrap steel obtained in step 1, so that the sulfide ore slurry is in full contact with the clean surface of the scrap steel, adding mineral processing return water to the sulfide ore slurry to be processed, so that galvanic corrosion occurs fully between the ore sample and the scrap steel, and obtaining a sulfide ore mineral sample after galvanic corrosion; Step 3: Transfer the sulfide ore sample obtained in step 2 to a flotation tank for flotation, control the stirring speed to be constant, add flotation reagents after stirring for a certain period of time to flotate the sulfide ore, and obtain flotation concentrate and tailings products.
2. The method for inhibiting sulfide ore flotation by utilizing scrap steel-sulfide ore galvanic corrosion according to claim 1, characterized in that: In step 1, the scrap steel material is pure iron scrap steel, low carbon steel scrap steel, medium carbon steel scrap steel or high carbon steel scrap steel.
3. The method for inhibiting sulfide ore flotation by utilizing scrap steel-sulfide ore galvanic corrosion according to claim 1, characterized in that: In step one, the surface of the scrap steel material is cleaned, specifically: ultrasonic cleaning and polishing the surface of the scrap steel material.
4. The method of suppressing sulfide ore flotation by utilizing scrap steel-sulfide ore galvanic corrosion according to claim 1, characterized in that: In step 1, for the severely oxidized scrap steel material, the rust on the scrap steel surface is removed by shot blasting, high-pressure water jet rust removal or laser rust removal.
5. The method for inhibiting sulfide ore flotation by utilizing scrap steel-sulfide ore galvanic corrosion according to claim 1, characterized in that: In step 2, during the galvanic corrosion process, the moisture content of the sulfide ore slurry is controlled within the range of 20% to 60%, the galvanic corrosion temperature is 20-80°C, and the galvanic corrosion time is 10-50 min.
6. The method of suppressing sulfide ore flotation by utilizing scrap steel-sulfide ore galvanic corrosion according to claim 5, characterized in that: In step 2, an electric heater or a solar heater is used to maintain the slurry temperature in the range of 20-80°C during the galvanic corrosion process.
7. The method of claim 1, wherein the method comprises: In step 2, during the galvanic corrosion treatment process, the slurry between the two scrap steels is evenly stirred once every 3-10 minutes, and stirred 1-3 times during the galvanic corrosion period, with a stirring time of 1 - 3 minutes. After stirring, the slurry is evenly applied on the clean surface of the scrap steel.
8. The method of suppressing sulfide ore flotation by utilizing scrap steel-sulfide ore galvanic corrosion according to claim 1, characterized in that: In step three, the flotation agent is methyl isobutyl carbinol frother.
9. The method of claim 1, wherein the method comprises: In step 3, the amount of flotation reagent added is 2-15 g / t.
Citation Information
Patent Citations
Device for purifying graphite by taking desulfuration residues as raw materials and processing technology
CN105129783A
Galvanic corrosion experimental device and experimental method for ore grinding medium and sulphide ore
CN116539506A
process for the preparation of cellular polymeric structures.
NL7503250A
Method and system for treating oily wastewater
US20120132588A1
AP200001755D0